Hospital service quality and patient loyalty: the mediation effect of empathy. Issue 8 (17th October 2018) - Zhang, Yucheng; Zhang, Long; Zhang, Xin; Yang, Miles M.; Zhang, Shanshan; Li, Shyh-Jane; Huang, Yu-Ying
Abstract : Purpose: Drawing on social identification theory, this research aims to explore an important mechanism – patients' perceived empathy from a hospital, which is defined as caring, individualized attention provided by the hospital – that explains how service quality influences patients' loyalty to the hospital. Design/methodology/approach: This study adopts a structural equation modelling framework to estimate the mediation relationship between service quality and patient loyalty using two studies based on hospital employees and patients. Findings: In Study 1, hospital staff survey data showed that service quality enhanced patients' perceived empathy from the hospital. In Study 2, the authors confirmed and extended the findings of Study 1 by using patient survey data that suggested that patients' empathy mediated the relationship between service quality and patients' loyalty to the hospital. Originality/value: The results of the two studies suggested that service quality increased patients' empathy, which in turn improved patients' loyalty to a hospital. The results extend the customer loyalty literature by exploring the critical antecedents and mechanisms of customer loyalty in the healthcare context. The studies interpret healthcare phenomena from the service aspect of fulfilling patients' unique needs and providing a good hospital service experience. Moreover, the authors offer an insightful approach to explaining the service quality–patient loyalty linkage in the healthcare industry. Important theoretical and managerial contributions and suggestions for future research are discussed.